ИННОВАЦИОННАЯ ДЕЯТЕЛЬНОСТЬ И МЕЖДУНАРОДНОЕ СОТРУДНИЧЕСТВО КАК ОСНОВА ПОВЫШЕНИЯ КАЧЕСТВА ОБРАЗОВАНИЯ (ART AND CULTURE BULLETIN, 2024)
The article examines the innovative activities and international cooperation of theDepartment of Russian Language and Literature. Innovation in education means improving the quality ofeducation at a university.
Keywords: education; modernization; competitiveness; paremiology; linguoculturology; concept; comparative studies; translation studies; literary criticism; comparative linguistics.